1998
DOI: 10.1159/000017353
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Effects of Multiple Acute Cocaine Injections on Maternal Behavior and Aggression in Sprague-Dawley Rats

Abstract: Rat dams, which had no prior drug treatment, were either nontreated controls or were injected subcutaneously 4 times during a 10-day period with a single dose of 30, 15 or 7.5 mg/kg of cocaine hydrochloride HCl, or normal saline. Injections were given immediately postpartum following delivery of their final pup (PPD 1), and again on postpartum day 3 (PPD 3), postpartum day 6 (PPD 6) and postpartum day 10 (PPD 10). Dams were observed 30 min following injections for maternal behavior (MB) towards 8 surrogate mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
63
1
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 29 publications
5
63
1
2
Order By: Relevance
“…Significant disruptions in maternal behavior following chronic gestational cocaine treatment during pregnancy were reported for the onset or very early post-partum period, and these dams did not display the hyperactivity often seen in acutely treated dams (Heyser, Molina, & Spear, 1992;Kinsley et al, 1994;Peeke, Dark, Salamy, Salfi, & Shah, 1994; Vernotica, Lisciotto, Rosenblatt, & Morrell, 1996). No reports, to our knowledge, have been published on intermittent gestational and postpartum cocaine treatment or the intergeneration effects of such treatment on maternal behavior.In previous studies, dams treated with cocaine gestationally were also found to exhibit differences in oxytocin system dynamics Johns, Lubin, Walker, Meter, & Mason, 1997;Johns, Nelson, et al, 1998;; Lubin, Elliott, Black, & Johns, 2003). Oxytocin is an important neuroendocrine system implicated in normal maternal behavior onset in rats (Fuchs, 1983;Pedersen et al, 1982;Pedersen, Caldwell, Johnson, Fort, & Prange, 1985;Pedersen et al, 1994) and therefore likely to be implicated when this behavior is disrupted (Pedersen et al, 1985; Van Leengoed, Kerker, & Swanson, 1987).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Significant disruptions in maternal behavior following chronic gestational cocaine treatment during pregnancy were reported for the onset or very early post-partum period, and these dams did not display the hyperactivity often seen in acutely treated dams (Heyser, Molina, & Spear, 1992;Kinsley et al, 1994;Peeke, Dark, Salamy, Salfi, & Shah, 1994; Vernotica, Lisciotto, Rosenblatt, & Morrell, 1996). No reports, to our knowledge, have been published on intermittent gestational and postpartum cocaine treatment or the intergeneration effects of such treatment on maternal behavior.In previous studies, dams treated with cocaine gestationally were also found to exhibit differences in oxytocin system dynamics Johns, Lubin, Walker, Meter, & Mason, 1997;Johns, Nelson, et al, 1998;; Lubin, Elliott, Black, & Johns, 2003). Oxytocin is an important neuroendocrine system implicated in normal maternal behavior onset in rats (Fuchs, 1983;Pedersen et al, 1982;Pedersen, Caldwell, Johnson, Fort, & Prange, 1985;Pedersen et al, 1994) and therefore likely to be implicated when this behavior is disrupted (Pedersen et al, 1985; Van Leengoed, Kerker, & Swanson, 1987).…”
mentioning
confidence: 98%
“…Their offspring are born blind, unable to thermoregulate, defecate, urinate, or protect themselves from attack (Numan, 1994), thus needing considerable maternal care to survive (Stern, 1997). Behaviorally and neurologically, maternal behavior in the rat has also been relatively well characterized (Numan, 1994;Pedersen, Ascher, Monroe, & Prange, 1982;Pedersen, Caldwell, Walker, Ayers, & Mason, 1994) so that any insult to normal maternal behavior can be easily determined.Maternal separation studies also support a rat intergenerational model of behavior showing that cross-fostering results in behavior of offspring similar to behavior of rearing dams, suggesting a nongenetic transmission of behavior (Francis, Diorio, Liu, & Meaney, 1999;Liu, Caldji, Sharma, Plotsky, & Meaney, 2000), which among other data led us to investigate the presence of intergenerational effects of cocaine use.As far as the literature to date, there is general agreement that acute cocaine treatment in rat dams disrupts both early onset and established pup-directed maternal behavior, while increasing locomotor behavior and stereotypies (Johns, Nelson, et al, 1998;Johns, Noonan, Zimmerman, Li, & Pedersen, 1994;Kinsley et al, 1994; Zimmerberg & Gray, 1992). Significant disruptions in maternal behavior following chronic gestational cocaine treatment during pregnancy were reported for the onset or very early post-partum period, and these dams did not display the hyperactivity often seen in acutely treated dams (Heyser, Molina, & Spear, 1992;Kinsley et al, 1994;Peeke, Dark, Salamy, Salfi, & Shah, 1994; Vernotica, Lisciotto, Rosenblatt, & Morrell, 1996).…”
mentioning
confidence: 99%
“…Chronic cocaine and CS dams received subcutaneous (sc) injections twice daily throughout gestation (GD 1-20) on alternating flanks, of 15 mg/kg cocaine HCL (dose calculated as the free base; Sigma Chemical Company, St. Louis, MO) dissolved in 0.9% normal saline (total volume 2 ml/kg), or normal saline (0.9%) respectively, at approximately 0800 and 1600. Intermittent cocaine-treated dams received the same dose and volume of cocaine as the CC dams, except that their injections only occurred on two consecutive days, every five days during gestation (GD 2,3,8,9,14,15,20) and on the same respective days during the postpartum period. Intermittent saline-treated dams received normal saline (0.9%) on the same injection schedule as the IC dams.…”
Section: Subjectsmentioning
confidence: 99%
“…The intermittent schedule was modeled after a previous study examining behavioral effects of prenatal cocaine exposure on offspring [19] and is designed to model intermittent usage patterns in humans. The IC treatment regimen was employed in addition to the CC treatment as previous research indicated differences in maternal behavior following either acute or intermittent cocaine treatment in dams [20,23,25,50,55] accompanied by differences in oxytocin (OT) system dynamics following the different treatment regimens [7,22]. UN dams were weighed and handled daily, but received no drug treatment.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation